JUNG AND EXISTENTIALISM - Ștefan BOLEA (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
In the following paper I will argue that there are interesting connections between the founder of analytical psychology, Carl Gustav Jung, and the school of existentialism. Analytical psychology and existentialism share almost the same Zeitgeist (becoming influential between the 1930’s and 1960’s) and are both interested in the concept of individuality. I would like to follow the liaison between Jung and existentialism regarding authenticity and death. First of all, the concept of authenticity deserves extensive treatment. Heidegger’s Das Man and Sartre’s mauvaise foi have an interesting companion in Jung’s notion of the persona, the psychological concept of the mask. Second of all, existentialist authenticity can be compared to the Jungian integration of the shadow. Moreover, the concept of death (Heidegger’s Sein-zum-Tode) can be compared with Jung’s understanding of death from The Red Book.